Effect of defect length on rolling contact fatigue crack propagation in high strength steel (Fracture and Structural Integrity, 2015)
The objective of the present paper is to clarify the effect of defect length in depth direction on rolling contact fatigue (RCF) crack propagation in high strength steel. RCF test and synchrotron radiation micro computed tomography (SR micro CT) imaging were conducted. In the case of the defect with the 15 ?m diameter, flaking life decreased with increasing defect length. In a comparison of the CT image and the SEM view, the shapes of defects and the locations of the horizontal cracks were almost the same respectively. The mechanism of RCF crack propagation was discussed by finite element (FE) analysis. Defects led to higher tensile residual stress than that without defects in the region where the defect exists. The shear stress range at 0.1 mm in depth on the middle line of the defect and the range of mode II stress intensity factor at the bottom of a vertical crack increased with increasing defect length.
Keywords: Rolling contact fatigue